Transformation in the Western Balkans: The readiness for a sustainable energy landscape - Ivana Vuchkova (University American College Skopje, 2020)
A review into the political trends and dynamics reveals that current energy developments are overwhelmingly influencing the political discourse and security dialogue in many regions. Though energy demands are demonstrating growing tendencies, the confrontation of climate change urges governments to collectively respond and decarbonize the energy systems through promotion of renewable energy sources, innovative technologies, and sustainable solutions. However, the complexity of the established energy networks and the strong lobbies of coal and other conventional sources in regions like the Western Balkans, represents an impediment to a smooth transformation. In a crucial momentum, all conditions point towards elevating the just energy transformation at the core of the political and cooperation dialogue on a regional level. The main aim of this paper is to provide a comprehensive analyses of the readiness of government policies to support of energy sources in the countries of Albania, Bosnia and Herzegovina, Kosovo, Montenegro, North Macedonia and Serbia. Furthermore, a more detailed focus will be given on the current conditions and challenges for promoting renewables within the legal context and undertaken obligations towards the international community, as well as the needs for adequate adaptation towards the expected changes in weather conditions due to climate change. The data used for the purpose of this research were collected from the official statistics records and public reports from relevant countries.
Keywords: 330; climate change; just energy transition; renewables; regional dialogue; Western Balkan.